The investigation of the role of oral-originated Prevotella-induced inflammation in childhood asthma - Yan, Tongtong; Bao, Yuling; Cao, Shuyuan; Jiang, Ping; Zhang, Zhan; Li, Lei; Kang, Yulin; Wu, Qian (Frontiers in Microbiology, 2024)
Background and objectives The oral and gut microbiota play significant roles in childhood asthma pathogenesis. However, the communication dynamics and pathogenic mechanisms by which oral microbiota influence gut microbiota and disease development remain incompletely understood. This study investigated potential mechanisms by which oral-originated gut microbiota, specifically Prevotella genus, may contribute to childhood asthma etiology. Methods Oral swab and fecal samples from 30 asthmatic children and 30 healthy controls were collected. Microbiome composition was characterized using 16S rRNA gene sequencing and metagenomics. Genetic distances identified potential oral-originated bacteria in asthmatic children. Functional validation assessed pro-inflammatory properties of in silico predicted microbial mimicry peptides from enriched asthma-associated species. Fecal metabolome profiling combined with metagenomic correlations explored links between gut microbiota and metabolism. HBE cells treated with Prevotella bivia culture supernatant were analyzed for lipid pathway impacts using UPLC-MS/MS. Results Children with asthma exhibited distinct oral and gut microbiota structures. Prevotella bivia, P. disiens, P. oris and Bacteroides fragilis were enriched orally and intestinally in asthmatics, while Streptococcus thermophilus decreased. P. bivia, P. disiens and P. oris in asthmatic gut likely originated orally. Microbial peptides induced inflammatory cytokines from immune cells. Aberrant lipid pathways characterized asthmatic children. P. bivia increased pro-inflammatory and decreased anti-inflammatory lipid metabolites in HBE cells. Conclusion This study provides evidence of Prevotella transfer from oral to gut microbiota in childhood asthma. Prevotella’s microbial mimicry peptides and effects on lipid metabolism contribute to disease pathogenesis by eliciting immune responses. Findings offer mechanistic insights into oral-gut connections in childhood asthma etiology.